Tracking Chinese CPI inflation in real time - Michael Funke; Aaron Mehrotra; Hao Yu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
With recovery from the global financial crisis in 2009 and 2010, inflation emerged as a major concern for many central banks in emerging Asia. We use data observed at mixed frequencies to estimate the movement of Chinese headline inflation within the framework of a state-space model, and then take the estimated indicator to nowcast Chinese CPI inflation. The importance of forward-looking and high-frequency variables in tracking inflation dynamics is highlighted and the policy implications discussed.
URN:NBN:fi:bof-201408072208
Keywords: C53; E31; E37; 330; Nowcasting; CPI inflation cycle; mixed-frequency modelling; dynamic factor model; China